The psychological experience of sickle cell disease in a Cameroonian adolescent living with her grandparents - Nsangou, Hassan Njifon; Mboe, Gustave Georges (Utan Kayu Publishing, 2024)
Sickle cell disease, the most widespread genetic disorder globally, is characterized by chronic and painful crises and high treatment costs, particularly in the Sub-Saharan African context where the disease is often associated with imminent death. This study aims to understand the experiences of an adolescent in Cameroon living with this disease and residing with her grandparents. Through in-depth interviews, we reveal how therapy non-compliance—particularly evident in medication delays—and the ambivalent behavior of her grandparents impact her disease management. The grandparents exhibit behaviors that are sometimes overprotective and at times aggressive, which not only affect how this adolescent understands and manages her condition but also hinder the process of subjectivation of her disease. These findings highlight the need to provide a space for grandparents to express their understanding of their granddaughter's illness and to assume their role in the care process. This study extends our understanding of family dynamics in managing sickle cell disease and demonstrates the importance of supporting grandparents as crucial resources in healthcare within this context.